Experimental Investigation of the Performance of a Household Refrigerator Using Phase Change Material - Jasim, Mqdad R.; Sultan, Hussien S.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2023)
A household refrigerator represents an essential device for all houses nowadays. The electric energy consumed by the refrigerator and the fluctuation of the temperature inside the fresh food cabin is the main two problems affecting its performance. Incorporating phase change material (PCM) inside the refrigerator is one of the solutions for the previous mentioned problems. In the present study, a water PCM is added to the cabinet of 220-litters double door refrigerator. The PCM (0.5 ml of water) is added at three different locations, touch the front of the evaporator part inside the cabin, touch the rear of the evaporator part in the cabin, and far away from the evaporator part inside the cabin. The location of the PCM determines how much energy is released and stored from the evaporator. The use of phase change material (PCM) touch to the evaporator increases the rate of heat transfer due to the conduction method being used throughout the whole heat transfer process from the evaporator to the phase change material (PCM), which raises the refrigeration system’s COP (coefficient of performance). The experimental test period is 24 hours for each day. Firstly, the refrigerator is tested without using PCM, and the power consumption, the temperatures at different points for the refrigerator, suction pressure, discharge pressure, the ambient temperature, and the time on period and time off period of the compressor are measured. Secondly, for same testing period all previous parameters are measured with using PCM at different locations inside the refrigerator. The results show that, adding the PCM (water) behind the evaporator led to increase the COP by 21.97%, increase the compressor off time by 73 minutes, reduction in power consumption of 14.4%, decrease of exergy losses of the system by 8% and temperature fluctuation reduced inside the fresh food cabin, that enhance the quality of stored food. Adding the PCM front the evaporator improve the previous parameters but less than that of the first case. The third location, adding the PCM far away from the evaporator has no improvement on the refrigerator’s performance.